ACUTE PULMONARY EMBOLISMS - Hariadi, Kartika Widayati Taroeno (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACTAcute pulmonary embolisms is a major cause of complications and death associated in surgery, medical illnesses, injury, and also may occurs after  a long-distance air travel. It is often originating from deep-vein thrombosis and has a wide spectrum of clinical manifestation ranging from asymptomatic, incidentally discovered emboli, to massive embolism causing immediate death. Incidence of pulmonary embolism ranges from 23-69 cases per 100,000 populations. Case fatality rates vary widely depending on the severity of the cases; at an average case fatality rate within 2 week of diagnosis of approximately 11%. It may have chronic sequele as post thrombotic syndrome and chronic thromboembolism pulmonary hypertension.            Acute pulmonary embolism is often difficult to diagnose. The predisposing factors for pulmonary embolisms consist of hereditary factors, acquired factors, and probable factors. Patients with symptoms of dyspnea, chest apnea, tachypnea or tachycardia arise suspiciousness of pulmonary embolisms therefore should be screened their probability for developing the disease. Low risk patients will then be evaluated for d-dimer test. Treatment should be initiated promptly in high risk patients, followed by imaging procedure evaluation. Chest radiographs, CT scan arteriography, VQ scan are performed to either include or exclude diagnosis of pulmonary embolisms.            Treatments consist of thrombolysis for acute and unstable massive pulmonary embolisms, and anticoagulation with heparin for stable acute pulmonary embolism. A meta-analysis of several major trials showed that low molecular weight heparin is at least as effective as unfractionated heparin in preventing the recurrence of venous thromboembolism events and at least as safe with respect to the rate of major bleeding.            This review will further describe in detail the pathomechanisms, diagnosis, and management of acute pulmonary embolisms.